Implantación de la contabilidad comercial en R y C Ferretería, del cantón Atahualpa, provincia de El Oro, periodo julio – septiembre 2014 - Unusungo Salinas, Jaime Danilo (2015)
THE"IMPLEMENTATION OF BUSINESSACCOUNTINGRYCHARDWARE, THECANTONATAHUALPA, PROVINCE OF GOLD,PERIODJULY - SEPTEMBER2014,"arises from thedemand andrequirementinformation required bygovernmentalinstitutions such as theSRI, IEESS, Ministry of Labour Relationsand others,economic information thatis needed inthis newcompetitive environment;tosupplycontrol meansand new financialconceptsbeforea financialdiagnosisto productivity, sustainabilityand businessempowerment, based on the systematization andbuildingcompetitive advantageas a toolfor generatingorganizational capacitywithfinancialperspectiveguidelines;and becausethisaccountingimplementationas thesisis a requirementto qualify for thedegree ofEngineerin Accounting and Auditing, CPA., at the National UniversityofLoja. The introduction ofcommercial accountinginvolved thefulfillment ofthe objectivesaimed atRandCHardwareCompany; subjectto observation andcompliance withaccounting, tax andlegal requirementswithtechnicaladdresses, which allowed us to presentfinancial statements andtaxobligations.Adequate and timely financialstatementsthat enableits ownerto takethenecessary correctivetovalidateor ratifycontrol actionsforbusiness developmentunderthe proposed institutionalobjectives. After theintroduction ofcommercial accountingin the companyRandCHardware,determinedthat Mr.PatricioDanielgaveRuilovaMalhaber, orderly andin accordancewith the rules andaccounting principlesaccounting process, recordsthat will help youknow theeconomic and financial situationof hisshop